Website-Based Academic Information System Design At Ma Bumi Persada Reviewed From The Designer Perspective Treasury Enterprise Architecture Framework (TEAF) - Irwan Dawil Fahmi; Sudin Saepudin (International Journal of Health Engineering and Technology, 2025)
This study aims to design a website-based Academic Information System at MA Bumi Persada by considering the designer's point of view using the Treasury Enterprise Architecture Framework (TEAF). TEAF was chosen as the framework because it provides comprehensive guidance for designing an integrated and efficient information system. The research method used is a literature study to understand the TEAF design principles and analyze the needs of an academic information system. Furthermore, a design analysis was carried out involving the identification of business processes, data structures, and user interfaces. The results of the analysis are the basis for designing an academic information system that is in accordance with the needs of MA Bumi Persada. At the design stage, the main focus is to create a structured system architecture that can be easily integrated. The user interface design is carried out by considering the optimal user experience. The application of web technology as a system base provides freedom of access and openness of information. This research is expected to contribute to improving operational efficiency and accessibility of information at MA Bumi Persada. The designed academic information system is expected to be able to support various academic activities, ranging from student management, scheduling, to reporting learning outcomes. With the application of TEAF, it is hoped that this information system can be scalable, flexible, and can develop in line with the needs of MA Bumi Persada in the future.